2022
DOI: 10.1097/inf.0000000000003748
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pneumococcal Disease in High-risk Children: A 10-Year Retrospective Study

Abstract: Background: Despite the availability of conjugate pneumococcal vaccines, children with high-risk conditions remain vulnerable to invasive pneumococcal disease (IPD). This study sought to describe IPD prevalence, vaccination and outcomes among high-risk children. Methods: We used International Classification of Disease10 discharge and microbiology codes to identify patients hospitalized for IPD at a large pediatric hospital from January 1, 2009, to December 31, 2018. Patients were considered high-risk if they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In Canada, despite recommendations to vaccinate high-risk children older than 2 years with PPSV23, only three patients had received PPSV23 among 66 patients with known pneumococcal vaccination status. These data suggest that most children with NS at high risk of IPD are incompletely vaccinated according to standard recommendations [9]. We have detected non-PCV13 serotypes in at least 25% of children with NS.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In Canada, despite recommendations to vaccinate high-risk children older than 2 years with PPSV23, only three patients had received PPSV23 among 66 patients with known pneumococcal vaccination status. These data suggest that most children with NS at high risk of IPD are incompletely vaccinated according to standard recommendations [9]. We have detected non-PCV13 serotypes in at least 25% of children with NS.…”
Section: Discussionmentioning
confidence: 67%
“…Each year, around 1-2% of patients with NS suffer from invasive bacterial infections, specifically pneumococcal infections including peritonitis, bacteremia, and pneumonia and sepsis continues to be a leading cause of death in children with NS [5][6][7][8]. Despite the availability of PCVs, children with high-risk conditions remain vulnerable to IPD [9]. Van Warmerdam et al [9] retrospectively evaluated IPD in high-risk children between 2000 and 2018 in Canada.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All but two patients in the CI group had a cefotaxime trough level concentration ≥2 mg/L, while it was undetectable (<2 mg/L) in all but five patients of the IA group. Our findings have major clinical implications, given the burden of severe infections and difficult to treat infections in patients with SCD[ 22 , 23 ]. Our results are in accordance with those of Maksoud et al who found very low attainment of target cefotaxime serum concentrations in pediatric SCD patients (only 5.6% of patients achieved 90% of time above the MIC of 2mg/L) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, the prevalence of children with chronic medical conditions has progressively increased with the risk of experiencing complications including more severe and long-term illness, hospitalization, and even death [ 1 , 2 , 3 ]. Moreover, it is well known that the introduction of vaccines, coupled with the implementation of programs aimed at universal infant immunization, have reduced the incidence of several vaccine-preventable diseases and their related complications [ 4 ].…”
Section: Introductionmentioning
confidence: 99%